2000
DOI: 10.1034/j.1399-3054.2000.100405.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant status of anoxia‐tolerant and ‐intolerant plant species under anoxia and reaeration

Abstract: The redox potential of the cell, as well as the antioxidant status of the tissue, are considered to be important regulatory constituents in an adaptive response in plants. Here the involvement of active antioxidants ascorbic acid (AA), reduced glutathione (GSH) and α‐ and β‐tocopherols in reactive oxygen species scavenging, and the effect of anoxic stress on their reduction state were studied in 4 anoxia‐tolerant and ‐intolerant plant species: Iris germanica L., Iris pseudacorus L., wheat (Triticum aestivum L.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(89 citation statements)
references
References 44 publications
2
80
0
2
Order By: Relevance
“…Phytochemicals are a class of compounds comprising a wide variety of molecules present in plants, including flavonoids which are known to possess significant health-promoting properties, generally related with their capabilities to act as chain-breaking antioxidants or as radical scavengers [1,2]. In fact, oxidative stress occurs upon disruption of the homeostatic balance between free radical generation and the natural antioxidant defence mechanisms (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemicals are a class of compounds comprising a wide variety of molecules present in plants, including flavonoids which are known to possess significant health-promoting properties, generally related with their capabilities to act as chain-breaking antioxidants or as radical scavengers [1,2]. In fact, oxidative stress occurs upon disruption of the homeostatic balance between free radical generation and the natural antioxidant defence mechanisms (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This shows that the steady state conditions are attained after three hours. The structure-activity relationship studies have shown that among other factors, the more the hydroxyl groups in a molecule the higher the antioxidant activity of that molecule 14,15 . Key: NT = Not tested…”
Section: Resultsmentioning
confidence: 99%
“…Wetland species (Iris pseudacorus, rice) produce a smaller amount of ROS and products of LPX under anoxic and post-anoxic stress than nonresistant ones (I. germanica, oats, wheat, Chirkova, Novitskay, and Blokhina, 1998;Blokhina, Fagerstedt, and Chirkova, 1999). Suppression of oxidative damage in hypoxia-resistant plants correlates with activation of antioxidant enzymes: peroxidase (Chirkova, Sokolovskaya, and Khazova, 1973;Chirkova and Sokolovskaya, 1976;Lastochkin, Yemelyanov, and Chirkova, 2000) and superoxide dismutase (Chirkova, Novitskaya, and Blokhina, 1998), accumulation of tocopherols (Chirkova and Gobedzhishvili, 1993;Chirkova, Novitskaya, and Blokhina, 1998;Blokhina et al, 2000), and turnover of ascorbic acid and glutathione (Blokhina et al, 2000). Thus, hypoxia-resistant plants demonstrate resistance to oxidative stress, too.…”
Section: Adaptation To Post-hypoxic/post-anoxic Reoxygenationmentioning
confidence: 99%